14‐month‐olds exploit verbs' syntactic contexts to build expectations about novel words. (9th July 2020) - Babineau, Mireille; Shi, Rushen; Christophe, Anne
Abstract: During their second year of life, infants develop a rudimentary understanding of grammatical categories based on their knowledge and use of frequent function words. The current study inquired whether, at only 14 months of age, infants can track co‐occurrence patterns between function words and content words (e.g., determiners can precede nouns, and pronouns can precede verbs), and use these previously encountered syntactic contexts to build expectations about which function words can co‐occur with novel words. Using a habituation paradigm, French‐learning 14‐month‐olds were presented with utterances containing two novel words preceded by function words (either two determiners in the Novel Nouns condition or two pronouns in the Novel Verbs conditions). We found that at test, infants looked longer during trials in which the novel words occurred in an unexpected syntactic context (following a pronoun for infants in the Novel Nouns condition and following a determiner for infants in the pooled analysis of the three Novel Verbs conditions). Hence, our results confirm previous findings on infants' sensitivity to noun contexts and most importantly demonstrate that their sensitivity to the co‐occurrence of verbs with pronouns begins much earlier than previously understood.